Incremental validity of the Child Behavior Checklist (CBCL) and the Strengths and Difficulties Questionnaire (SDQ) in Vietnam - Dang, Hoang-Minh (Asian J Psychiatr, 2017)
OBJECTIVE: Valid but efficient psychiatric assessment is essential for mental health development in Asian low and middle-income countries. This study’s objective was to assess the validity of Vietnamese versions of the Child Behavior Checklist (CBCL), and the Strengths and Difficulties Questionnaire (SDQ) in Vietnam. METHODS: Measures were completed by a community sample of 1314 parents of children 6–16 years old from 10 Vietnamese provinces, and by parents of 208 children recruited from 3 psychiatric facilities in Hanoi. RESULTS: Internal consistency was in the fair to excellent range for all CBCL scales (.76–.96) and for the SDQ Total Problems scale (.81); SDQ subscale internal consistency was in the poor to fair range (.31–.73). All CBCL and SDQ scales and most individual items significantly discriminated between referred and non-referred children, with referred children scoring in the more pathological direction; the CBCL had significantly larger referral effect sizes than the SDQ for all four pairs of comparable scales. At the item level, the largest referral status effect for the CBCL were #73 (Sexual Problems), #84 (Strange Behavior), and #91 (Talks about suicide), and for the SDQ they were #10 (Constantly fidgeting), #15 (Easily Distracted) and # 25 (Good Attention Span-reverse scored). Five CBCL (#2 Drinks alcohol; #99 Uses tobacco, #32 Has to be perfect; #53 Overeats; #56A Aches and pains) and one SDQ items (#23 Gets along better with adults than children) did not discriminate referral status, suggesting the influence of cultural values on clinical referrability (e.g., that Vietnamese parents may not see use of tobacco as an issue of concern, or related to health). CONCLUSIONS: There is good support for the reliability and validity of the Vietnamese version of the CBCL, and for the SDQ Total Problems scale. Overall, the CBCL appears to be the stronger measure psychometrically, particularly if in-depth assessment is needed.